Characterization of the novel HLA‐A*11:280 allele by next‐generation sequencing in a Chinese cord blood donor. (20th January 2020) - Dong, Lina; Wang, Fang; You, Xuan; He, Ji; Zhu, Faming
Abstract : HLA‐A*11:280 differs from HLA‐A*11: 01: 01: 01 by a single nucleotide substitution at position 982 G>T.